The Effect of Special Exercises to Develop Agility and the Kinetic Response Speed of Individual Defense in the Free Throw Area for Basketball Players Ages 15-17 Years - Qahtan Mohammed, Nawfal (International Journal of Psychosocial Rehabilitation, 2020)
The study objective to identify the effect of special exercises to develop agility and the speed of the kinetic response of individual defense in the free throw area for basketball players ages 15-17 years, and the assumption of the study was the presence of moral differences in favor of the experimental group that carried out special exercises for individual defense within the limits of the free throw area, the researcher used the experimental approach on a sample of 12 players representing Al-Anbar Sports Club for junior basketball for the year 2019- 2020, and the study reached results that the special exercises had a positive impact on the agility of the side steps and the speed of the kinetic response selectively for the youth of The basketball study recommended focusing on special exercises to develop the capabilities of individual guns.